Disturbing Load Classification Based on the Grey Relational Analysis Method and Load Performance Index - Moreira, Alexandre C.; de Souza, Wesley A.; Conrado, Bruna R. P.; Morales-Paredes, Helmo K. [UNESP] (Springer Nature, 2020)
This paper proposes an approach based on grey relational analysis to analyze and classify potentially disturbing loads taking into account the power factor, unbalance, harmonics and reactive power. By computer simulations, a set of loads with different characteristics were analyzed through various load performance indexes. Using the grey relational analysis applied to load performance indexes, such disturbances can be quantified; to carry out the load assessment; to help adopt energy billing policies; to support power quality control, grid management, as well as to provide information to the electric utility about analyses and decision making regarding the preventive maintenance of the grid for improved reliability and efficiency. Finally, the method was applied in practice to evaluate real disturbing loads in various industries with power quality problems.
Keywords: Grey relational analysis; Harmonic distortion; Power factor; Power quality and unbalance